2019
DOI: 10.3389/fenrg.2019.00032
|View full text |Cite
|
Sign up to set email alerts
|

Lifecycle Environmental Impact Assessment of an Overtopping Wave Energy Converter Embedded in Breakwater Systems

Abstract: Overtopping breakwater systems are among the most promising technologies for exploiting wave energy to generate electricity. They consist in water reservoirs, embedded in piers, placed on top of ramps, higher than sea-level. Pushed by wave energy, seawater fills up the reservoirs and produces electricity by flowing back down through low headhydro turbines. Different overtopping breakwater systems have been tested worldwide in recent years. This study focuses on the Overtopping BReakwater for Energy Conversion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 46 publications
0
34
0
Order By: Relevance
“…Geographical distribution of the selected LCA studies, as shown in Table 1, indicates that 11 systems are installed in European seas [3,9,11,[13][14][15][16][17][18][19]22,23], 1 in New Zealand [12], 1 in China [20] and 1 in multicontinental locations [22]; three are located at hypothetical offshore locations [4,21,24].…”
Section: Spatial Distribution Of Studied Wave and Tidal Energy Systemsmentioning
confidence: 99%
See 4 more Smart Citations
“…Geographical distribution of the selected LCA studies, as shown in Table 1, indicates that 11 systems are installed in European seas [3,9,11,[13][14][15][16][17][18][19]22,23], 1 in New Zealand [12], 1 in China [20] and 1 in multicontinental locations [22]; three are located at hypothetical offshore locations [4,21,24].…”
Section: Spatial Distribution Of Studied Wave and Tidal Energy Systemsmentioning
confidence: 99%
“…As shown in Figure 1, the selected literature studied two oscillating surge WECs [22,25], one oscillating water column [21], three attenuators [14][15][16][17], two overtopping [3,23], four point absorbers [4,19,20,22], one vertical axis tidal [9], eight horizontal axis tidal [11][12][13]25], one Archimedes [13] and one tidal range [25].…”
Section: Spatial Distribution Of Studied Wave and Tidal Energy Systemsmentioning
confidence: 99%
See 3 more Smart Citations